(untitled) (INNOVATIVE ECONOMY, 2023)
Lytovka V.A., Prushkivska E.V., Pylypenko H.M. CORPORATE CULTURE TRANSFORMATION OF THE METALLURGICAL INDUSTRY ENTERPRISES AMID DIGITAL AND GREEN ECONOMY Purpose. The aim of the article is to reveal the peculiarities of the corporate culture transformation of the metallurgical industry enterprises amid digital and green economy. Methodology of research. General scientific and special methods of economic research were used in the process of conducting the research, in particular: a systematic approach – for determining the essence of corporate culture; sociological survey – for diagnosing the corporate culture of metallurgical enterprises; statistical methods – for processing the survey results and calculating Cronbach’s Alpha parameters to determine the reliability of the questionnaire; comparative method – to compare deviations between existing and desired profiles of corporate culture under the influence of digitalization, smartization and environmentalization; dialectical, abstract and logical – for making theoretical generalizations and forming conclusions. Findings. A methodology for diagnosing of the corporate culture transformation of the metallurgical industry enterprises under the influence of digitalization, smartization and environmentalization is proposed on the basis of a sociological survey of the staff of metallurgical enterprises of Ukraine. The results of the survey based on the profiles of the existing and desired corporate culture are demonstrated. The results of the survey proved that the staff of metallurgical enterprises PJSC "Zaporizhstal" (Zaporizhia), PJSC "INTERPIPE" (Dnipro), PJSC "Central GZK" (Kryvyi Rih), PJSC "KAMET-STEEL" (Kamianske), PJSC "YUZHKOKS" (Kamianske) want to reduce the gap between the existing and desired corporate culture in the direction of digital smart and green economy. Directions for improving the corporate culture of metallurgical enterprises under the influence of digitalization, smartization and environmentalization are recommended. Originality. A methodical approach to evaluating the transformation of corporate culture under the influence of digitalization, smartization and environmentalization (existing and desired) was developed. The approach includes five stages: 1) conducting a sociological survey; 2) calculations of integral indices; 3) three profiles formation of the corporate culture transformation of metallurgical enterprises; 4) calculation of the level of deviation of the desired from the existing culture and their comparison; 5) development of recommendations for the corporate culture transformation. Practical value. The proposed recommendations can be used to improve the mission, strategic vision, corporate culture and its values for metallurgical enterprises. Key words: Corporate culture, transformation, digital economy, green economy, green innovation, enterprise, smart metallurgical industry, sociological survey.